ANALYSIS THE INFLUENCE OF SOCIETY CULTURAL ON INTENTIONS TO START UP NEW BUSINESS ( CASE STUDY: MANADO SOCIETY) - Fauzi, Ismul (Sam Ratulangi University, 2015)
ABSTRACT Â This research investigates the influence of society cultural on intention to start up new business in Manado city. Researcher shall to know how many people in Manado city interesting with entrepreneurship. Researcher used elements of society cultural like power distance, collectivism and individualism as independent variables and motivator and intentions as dependent variables to analyze the relationship between society cultural and entrepreneurship. 300 people of Manado city were surveyed as respondents. All indicators were measured on a 5-point scale from 1: â€œstrongly disagreeâ€ to 5: â€œstrongly agreeâ€. The study has used structural equation model (SEM) methodology to investigate data and check developed hypotheses. The results of this study show that there are significant influence from the variables power distance and individualism factors on motivators and intentions to start up new business. Also, there no significant influence of collectivism factors toward intentions to start up new business. Keywords: Power Distance, Collectivsm, Motivators, Intention, Entrepreneurship, Culture